2016
DOI: 10.1007/s12640-015-9593-1
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenylate Cyclase Activating Polypeptide, A Potential Therapeutic Agent for Diabetic Retinopathy in Rats: Focus on the Vertical Information Processing Pathway

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) is a neurotrophic and neuroprotective peptide that has been shown to exert protective effects in different neuronal injuries, such as retinal degenerations. Diabetic retinopathy (DR), the most common complication of diabetes, affects the microvasculature and neuronal architecture of the retina. We have proven earlier that PACAP is also protective in a rat model of DR. In this study, streptozotocin-induced DR was treated with intravitreal PACAP administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…Degradation of PACAP1-38 in Systane ® Ultra at RT and +4°C (e). Higher stability was found at +4°C, similar to the other examined media kainate-and glutamate-induced excitotoxicity (Atlasz et al 2009;Seki et al 2006), UV light-induced lesion (Atlasz et al 2011), lipopolysaccharide-induced inflammation (Vaczy et al 2018), oxygen-induced retinopathy of prematurity (Kvarik et al 2016), diabetic retinopathy (D'Amico et al 2017;Szabadfi et al 2016) and high intraocular pressureinduced retinopathy (Seki et al 2011).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Degradation of PACAP1-38 in Systane ® Ultra at RT and +4°C (e). Higher stability was found at +4°C, similar to the other examined media kainate-and glutamate-induced excitotoxicity (Atlasz et al 2009;Seki et al 2006), UV light-induced lesion (Atlasz et al 2011), lipopolysaccharide-induced inflammation (Vaczy et al 2018), oxygen-induced retinopathy of prematurity (Kvarik et al 2016), diabetic retinopathy (D'Amico et al 2017;Szabadfi et al 2016) and high intraocular pressureinduced retinopathy (Seki et al 2011).…”
Section: Discussionsupporting
confidence: 75%
“…It affects tear secretion (Nakamachi et al 2016), influences muscle responses of the iris (Yamaji et al 2005), increases blood flow in the eye (Dorner et al 1998) and regulates pigment epithelial cell functions (Fabian et al 2012(Fabian et al , 2019Maugeri et al 2019a). Most importantly, as a general protective peptide found not only in the central nervous system but several peripheral organs as well (Laszlo et al 2019;Liu et al 2019;Polanco and Pennuto 2018;Reglodi et al 2018d, e;Shioda et al 2019;Szegeczki et al 2019), PACAP has been shown to exert diverse retinoprotective effects in models of toxic, ischemic, inflammatory and traumatic retinal injuries (Atlasz et al 2016(Atlasz et al , 2019Cheng et al 2018;Endo et al 2011;Gabriel et al 2019;Kvarik et al 2016;Seki et al 2008;Szabadfi et al 2016;Vaczy et al 2016;Ye et al 2019a, b). Several retinal cell types can be protected by PACAP, including ganglion cells, bipolar neurons, amacrine and pigment epithelial cells (Atlasz et al 2008;Fabian et al 2019;Maugeri et al 2019a;Szabadfi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Pituitary adenylate cyclase activating peptide has been reported to exert neuroprotective functions in a variety of retinal injuries 21 and in the retina of streptozotocin-treated rats. 23,49,50 Regarding possible direct effects on VEGF, most experimental evidence reports an inducing, and not inhibitory, effect of PACAP on VEGF. Indeed, PACAP treatment results in increased VEGF in rat retinal hypoperfusion, 51 in lung cancer cells, 52 and in pituitary folliculostellate cells.…”
Section: Discussionmentioning
confidence: 99%
“…The selective degeneration of related structures such as bipolar and ganglion cells could be ameliorated by PACAP treatment. In summary, intravitreal administration of PACAP may have therapeutic potential in streptozotocininduced DR through maintaining synapse integrity in the vertical pathway [ 94 ].…”
Section: Diabetic Retinopathy In the Retinamentioning
confidence: 95%